2023
DOI: 10.1097/wco.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic amyotrophic lateral sclerosis: from characterization to prevention

Abstract: Purpose of review Significant progress in characterizing presymptomatic amyotrophic lateral sclerosis (ALS) is ushering in an era of potential disease prevention. Although these advances have largely been based on cohorts of deep-phenotyped mutation carriers at an elevated risk for ALS, there are increasing opportunities to apply principles and insights gleaned, to the broader population at risk for ALS [and frontotemporal dementia (FTD)]. Recent findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Given that the overlap of the neurodegenerative pathologies we see in MMC children are reported both in unimpaired and cognitively impaired older populations (Wakisaka et al, 2003;Kovacs et al, 2013;Boyle et al, 2018;Nag et al, 2018;Wennberg et al, 2019;Karanth et al, 2020;Robinson et al, 2023), early neurotoxic environmental factors must be identified, and preventive interventions executed in highly exposed populations. Moreover, early identification of pre-symptomatic stages, the definition of early progression and heterogeneity of the quadruple neurodegenerative hallmarks, and the contribution of brain structural changes to early neuropsychiatric symptoms need to be described (Benatar et al, 2023;Busy et al, 2023;Butler Pagnotti et al, 2023;Kapustin et al, 2023;Manca et al, 2023;Montero-Calle et al, 2023;Russell and Rohrer, 2023;Ulugut et al, 2023;Young et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the overlap of the neurodegenerative pathologies we see in MMC children are reported both in unimpaired and cognitively impaired older populations (Wakisaka et al, 2003;Kovacs et al, 2013;Boyle et al, 2018;Nag et al, 2018;Wennberg et al, 2019;Karanth et al, 2020;Robinson et al, 2023), early neurotoxic environmental factors must be identified, and preventive interventions executed in highly exposed populations. Moreover, early identification of pre-symptomatic stages, the definition of early progression and heterogeneity of the quadruple neurodegenerative hallmarks, and the contribution of brain structural changes to early neuropsychiatric symptoms need to be described (Benatar et al, 2023;Busy et al, 2023;Butler Pagnotti et al, 2023;Kapustin et al, 2023;Manca et al, 2023;Montero-Calle et al, 2023;Russell and Rohrer, 2023;Ulugut et al, 2023;Young et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A significant elevation of the neurofilament light chain (NfL) in cerebrospinal fluid (CSF) and serum was found in ALS patients, compared to healthy controls. Increased values were found particularly in ALS patients with known mutations but have also been applied to sALS patients and may shorten the diagnostic delay by up to 3 months [20]. ALS is characterized by increased CSF and serum levels of NfL, a marker of neuroaxonal degeneration [216,217] that may be associated with CI [218].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that presymptomatic disease is not uniformly clinically silent with mild motor, cognitive and/or behavioral impairment, representing a prodromal stage of ALS [20]. In contrast to motor functioning that declines concomitantly with disease progression, cognitive deficits appear in early disease, are essentially present at the initial visit and usually do not substantially decline on follow-up [46].…”
Section: Cognitive Abnormalities In Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…More to that, when the speed of diagnostic neuropsychological tests was adjusted for dysarthria, no significant difference between spinal and bulbar onset was found [ 224 ]. Detecting and monitoring CI in ALS early on is essential not just for prognostic reasons, but also because it could have significant implications for future clinical trials [ 229 ].…”
Section: Cognitive and Neuropsychiatric Symptomsmentioning
confidence: 99%